2019
DOI: 10.1002/cssc.201901934
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Decarbonylation of Biomass‐Derived Aldehydes using Pd‐Doped Hydrotalcites

Abstract: Scheme1.Decarbonylation strategy for converting lignocellulose to platform chemicals HMF,furfural, furfuryl alcohol, and furan.[a] Dr.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…also observed the labile nature of the aldehyde (−CHO) group of 5‐HMF under Pd/Al 2 O 3 catalyst conditions under compressed CO 2 and got furfuryl alcohol as major product at 145 °C (Scheme 1b) [15] . Similarly, decarbonylation of 5‐HMF also noticed under microwave assisted flow conditions using Pd‐Hydrotalcite as catalyst [16] . In literature, maximum reports have been published on the decarbonylation of 5‐HMF and furfural, derived by heterogeneous Pd catalysts.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…also observed the labile nature of the aldehyde (−CHO) group of 5‐HMF under Pd/Al 2 O 3 catalyst conditions under compressed CO 2 and got furfuryl alcohol as major product at 145 °C (Scheme 1b) [15] . Similarly, decarbonylation of 5‐HMF also noticed under microwave assisted flow conditions using Pd‐Hydrotalcite as catalyst [16] . In literature, maximum reports have been published on the decarbonylation of 5‐HMF and furfural, derived by heterogeneous Pd catalysts.…”
Section: Methodsmentioning
confidence: 74%
“…[15] Similarly, decarbon-ylation of 5-HMF also noticed under microwave assisted flow conditions using Pd-Hydrotalcite as catalyst. [16] In literature, maximum reports have been published on the decarbonylation of 5-HMF and furfural, derived by heterogeneous Pd catalysts. More recently, Wu et al reported the decarbonylation of aldehyde group from 5-HMF and its in situ participation in carbonylative esterification with aryl iodide, Rh(cod)BF 4 as catalyst and DPPP as ligand for furfuryl esters synthesis.…”
mentioning
confidence: 99%
“…Recently we reported the high activity of heterogeneous catalysts based on Pd-doped hydrotalcites (Pd-HTs) for selective decarbonylation of aldehydes. 4 In the course of this study we observed that a,b-unsaturated aldehydes decarbonylate faster than aromatic and saturated aliphatic aldehydes. Given that hydortalcites, composed of metal hydroxide sheets sandwiched by anions and water, have basic sites, they can promote aldol condensation.…”
mentioning
confidence: 66%
“…The by-product 7c might have formed from 7 by a decarbonylation reaction in the presence of the Lewis acid sites of Ar-O-Hf and the solvent 2-PrOH. 59 Besides the target product and the detectable byproducts mentioned above, humins were another important class of byproducts (3b, 6b, 8b and 9b). 60 Overall, these results showed that Hf-TA was efficient for the conversion of various substrates with different structures.…”
Section: Catalyst Screening and Characterizationmentioning
confidence: 99%